A comparative multi-tiered immunogenicity assessment of biosimilar pegylated filgrastim: validation of methods for clinical assessment of INTP5. (1st February 2022) - Hajela, Pallavi; Patel, Ronak; Kale, Prashant; Kumar, Manish; Khambhampaty, Sridevi
ABSTRACT: Background and Objective: Validated and highly sensitive assays are required for comparative assessment of immunogenicity of biosimilars. For INTP5, a biosimilar pegylated filgrastim, the immunogenicity assessment included tiers that allowed for assessment of antibodies against the PEG and the Filgrastim moieties for comparative clinical immunogenicity assessment. Methods: Electrochemiluminescence immunoassay (ECLIA) was used for Screening, Specificity, and Titer assays for detecting anti-drug antibodies (ADAs) and cell-based method for neutralizing ADAs. The methods were validated to enable use of same methods irrespective of biosimilar or reference arms. Results: The ADA and cell-based assay for neutralizing antibody detection were validated with a sensitivity capable of detecting binding Anti-Pegfilgrastim antibody at 40 ng/mL and Neutralizing antibody at 380 ng/mL and used for a comparative immunogenicity study. Of 194 subjects, 10 subjects had confirmed positive anti-drug-antibody in the biosimilar arm and 9 in the reference arm. None of the subjects were detected with neutralizing anti-drug antibodies. Conclusion: This work demonstrates the application of a rigorous approach toward validation of assays for immunogenicity studies for biosimilars. Highly sensitive, precise, and robust assays were used to conclude comparable low incidences of anti-drug antibodies in both biosimilar and innovator arms of the clinical study for Pegfilgrastim.